1980
DOI: 10.1037/h0085928
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive, assertive, and insight-oriented group therapies in the treatment of reactive depression in women.

Abstract: Thirty-three non-psychotic, non-suicidal women (mean age 35.1 years) who scored between 15 and31 on the Beck Depression Inventory and whose depression was situationally related were assigned to either six week cognitive, assertive or insight-oriented group therapy. Subjects were administered a standardized interview, the Beck Depression Inventory, Rathus Assertiveness Schedule, Personality Data Form, and four tape recorded scenes requiring an assertive response before and after the groups and at a two month fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0

Year Published

1985
1985
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 22 publications
(10 reference statements)
1
15
0
Order By: Relevance
“…In contrast, LaPointe and Rimm (1980) and Peterson and Halstead (1998) reported that initial depression level was not a significant predictor of improvement. However, these authors did not use regression analyses, which may account for why they drew different conclusions.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…In contrast, LaPointe and Rimm (1980) and Peterson and Halstead (1998) reported that initial depression level was not a significant predictor of improvement. However, these authors did not use regression analyses, which may account for why they drew different conclusions.…”
Section: Discussionmentioning
confidence: 84%
“…However, these authors did not use regression analyses, which may account for why they drew different conclusions. LaPointe and Rimm (1980), for example, correlated the amount of change in the BDI with posttreatment BDI and found that these two variables were not significantly correlated. Peterson and Halstead grouped participants according to whether or not their initial BDI score exceeded 10 or 17.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies tended to show negligible differences between PDT and CBT, but the trials were too small and reporting too limited to permit reliable inferences about equivalence or even superiority . If CBT is superior to PDT, it is so only in very brief (8‐session) implementations .…”
Section: Depressionmentioning
confidence: 99%
“…Another outcome study examining the efficacy of group assertiveness training compared to traditional group psychotherapy in treating depression found that at one-month follow-up, the assertiveness group displayed increased self-reported comfort with assertiveness and greater likeliness to engage in assertive behaviors compared to a traditional psychotherapy group (Sanchez et al, 1980). In addition to improvement in depressive symptoms and increased assertive behavior, LaPointe and Rimm (1980) found that depressed women assigned to assertiveness training, compared to cognitive or insightoriented treatment, displayed more rational thinking and acceptance, and were significantly less likely to seek out further treatment at follow-up. In addition to improvement in depressive symptoms and increased assertive behavior, LaPointe and Rimm (1980) found that depressed women assigned to assertiveness training, compared to cognitive or insightoriented treatment, displayed more rational thinking and acceptance, and were significantly less likely to seek out further treatment at follow-up.…”
Section: Depressionmentioning
confidence: 99%